Systemic Granulomatosis in Guppies Poecilia reticulata - Areechon, Nontawith; Chansue, Nantarika; Ponpornpisit, Aranya; Yoshida, Terutoyo; Endo, Makoto (Agriculture and Natural Resources, 2001)
In many guppy Poecilia reticulata farms in the vicinity of Bangkok, diseases have caused longlasting fish death and consequently large cumulative mortality. Diseased guppies were collected and subjected to histopathological analysis. The analysis revealed systemic granulomatosis as a remarkable histological sign. Rod-shaped bacterial cells with strong acid-fastness were found in the granulomas. Therefore, this disease was diagnosed as acid-fastness bacterial infection. The acid-fastness bacterium infection seems to predispose various infections in the critical stage of the disease.